Mechanical Model of the Bee Bread Granules Separation Process in a Rotary Extractor (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
This paper presents a mechanical model describing the impact interaction between a rotor hammer and the wax cells of honeycombs during the separation of bee bread granules. An analytical dependence was obtained for determining the maximum impact force Pmax through the impact impulse, hammer mass, rotor angular velocity, and contact duration. A criterion of selective wax destruction while preserving the integrity of bee bread granules was proposed, based on the relationship between the strength limits of the contacting materials. The optimal range of rotor angular velocity (ω=30–45 s−1) and geometric parameters of hammers (edge rounding radius 2–3 mm) ensuring effective extraction without damaging the granules were determined. The model limitations were analyzed, including the absence of friction, localized deformation, simultaneous multi-point contact, and the need to refine stiffness parameters k and pk under varying humidity or temperature conditions. The obtained results can be applied to the optimization of rotary extractor designs and improvement of mechanical bee bread extraction efficiency.
Keywords: bee bread; rotary extractor; impact interaction; mechanical model; Hertz contact; impact force; failure criterion.